MANAJEMEN KESISWAAN - Ria Sita Ariska (Manajer Pendididikan, 2015)
The Purpose of this study was to describe the student’s management at senior high school number 2 Lubuklinggau. This study used descriptive qualitative research methods. The datawere collected by means of interview, observation and study documentation. Researchers obtain data by interviewing principal, vice principals and student areas of the curriculum, some teachersand administrative staff as well as students. The results of this research show that the management of student this school has been progressing well in accordance with the plan set by the school.Keywords: management and students